Development of a Dementia Education Workshop for Prison Staff, Prisoners, and Health and Social Care Professionals to Enable Them to Support Prisoners With Dementia. (April 2020) - Brooke, Joanne; Rybacka, Monika
The world's prison population is aging. Older prisoners, those aged 50 years and older, are at risk of poor health and developing a dementia. Prisoners with dementia may present challenges to the regime within the prison and require extra support. However, prison staff and health and social care professionals have reported a lack of skills and knowledge to identify and support prisoners with dementia. This may be due to a lack of dementia education programs developed specifically for the prison setting and delivered comprehensively for all who work with prisoners. The aim of this article is to describe the development and implementation of a dementia education workshop for the prison setting that is suitable for all prison staff, prisoners, and health and social care professionals.